Digital interventions for adults with schizophrenia in clinical settings: A scoping review - Indra Maulana; Iwan Shalahuddin (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Schizophrenia is a severe mental disorder that substantially affects quality of life and is associated with frequent relapse and poor treatment adherence. Although pharmacological treatment remains the cornerstone of schizophrenia management, digital technology-based interventions have increasingly been explored as complementary approaches to improve clinical and psychosocial outcomes. Purpose: To identify and map the types of digital technology-based interventions used for the management of schizophrenia among adults in clinical settings and to describe the role of nurses in their implementation. Method: A scoping review design following the Arksey and O'Malley framework, refined by the Joanna Briggs Institute, and reported according to the PRISMA-ScR guidelines. Literature searches were conducted in PubMed, Scopus, and ScienceDirect using the Population–Concept–Context framework. Primary studies published in English or Indonesian between 2019 and 2026 were included. From 13,637 identified records, 17 studies met the eligibility criteria and were analysed using descriptive and narrative synthesis. Results: The included studies evaluated various digital interventions, including mobile applications, web-based platforms, virtual reality, telehealth, videoconference-delivered cognitive behavioural therapy, and other digital technologies. Several studies reported improvements in psychotic symptoms, cognitive functioning, treatment adherence, patient engagement, and quality of life. However, some interventions showed limited or no statistically significant improvements in specific clinical outcomes, indicating variability in effectiveness across intervention types and study settings. Across the included studies, nurses were consistently identified as facilitators of digital intervention implementation through patient education, digital literacy support, monitoring, and coordination of care. Conclusion: Current evidence suggests that digital technology-based interventions may support schizophrenia management in clinical settings, although their reported effectiveness varies across intervention modalities and outcomes. Further high-quality studies are needed to determine the most effective approaches and to support the integration of digital interventions into routine psychiatric nursing practice. Keywords: Digital interventions; Health technology; Psychiatric nursing; Schizophrenia; Scoping review.